Public authority procurement strategy - Hodgkinson, David (Thomas Telford, 2001)
Authorities must procure goods and services in an effective manner, getting value for money and continuously improving performance. This new book interprets statutory Best Value requirements to provide a practical guide for Authority Members and staff as to the right way to choose a procurement strategy.